Where on the face do we look during phonemic restoration: An eye-tracking study - Baron, Alisa; Harwood, Vanessa; Kleinman, Daniel; Campanelli, Luca; Molski, Joseph; Landi, Nicole; Irwin, Julia (Frontiers in Psychology, 2023)
Face to face communication typically involves an audio (heard) and visual components to the speech signal. To examine the effect of task demands on gaze patterns in response to a speaking face, adults participated in two eye-tracking experiments with an audiovisual (articulatory information from the mouth was visible) and a pixelated condition (articulatory information was not visible). Further, task demands were manipulated by having listeners respond in a passive (no response) or an active (button press response) context. The active experiment required participants to discriminate between speech stimuli and was designed to mimic environmental situations which require one to use visual information to disambiguate the speaker’s message, simulating different listening conditions in real-world settings. Stimuli included a clear exemplar of the syllable /ba/ and a second exemplar in which the formant initial consonant was reduced creating an /a/-like consonant. Consistent with our hypothesis, results revealed that the greatest fixations to the mouth were present in the audiovisual active experiment and visual articulatory information led to a phonemic restoration effect for the /a/ speech token. In the pixelated condition, participants fixated on the eyes, and discrimination of the deviant token within the active experiment was significantly greater than the audiovisual condition. These results suggest that when required to disambiguate changes in speech, adults may look to the mouth for additional cues to support processing when it is available.